Design and Evaluation of an Exergaming System for Children With Autism Spectrum Disorder: The Children’s and Families’ Perspective - Graham, T. C. Nicholas; King, Nia; Coo, Helen; Zabojnikova, Pavla; Gurd, Brendon J.; Samdup, Dawa (Frontiers in Virtual Reality, 2022)
Children with autism spectrum disorder (ASD) have lower levels of physical activity than their typically developing peers. Barriers to participation include deficits in motor function and in social interaction, both of which reduce opportunities to engage in leisure activities that incorporate physical exertion. Because children with ASD also have higher than average levels of media use, exergames--video games that require bodily interaction to play--are a promising form of exercise. While studies have examined exergaming interventions for children with ASD, to date there has been little research on exergames that have been specifically designed for children with neurodevelopmental disorders, or qualitative analysis of players' and families' experience with exergaming programs. In this paper we present Liberi, an exergaming system involving kinaesthetic interaction within a virtual world, and designed explicitly for children with neurodevelopmental disorders. We report the results of a six-week study where Liberi was played from the home by five children with ASD. The paper describes those aspects of the design that were successful and unsuccessful; how children and parents viewed the exergames; how the games were incorporated into the children's lives; and how parents envisaged exergames could be best deployed for children with ASD.